Zinc‐Dithizone Complex Engineered Upconverting Nanosensors for the Detection of Hypochlorite in Living Cells. Issue 35 (6th July 2015) - Mei, Qingsong; Deng, Wei; Yisibashaer, Wuerzha; Jing, Huarong; Du, Guoqing; Wu, Ming; Li, Bing Nan; Zhang, Yong
<x xml:space="preserve">Abstract</x> Current chemo/biosensors for hypochlorous acid or hypochlorite detections are usually limited to the submicromolar level because of their insufficient sensitivity, which is a problem because the concentrations in biological matrices is generally on the nanomolar scale or even lower. Developing a probe with a high enough sensitivity remains a challenge. Using the minimal background fluorescence of upconversion nanocrystals to our advantage, we herein report on an energy‐transfer mechanism‐based upconversion luminescent nanosensor for the sensitive and selective detection of hypochlorite in aqueous solution. In this nanosensor water‐dispersible upconversion nanoparticles act as the energy donor and a novel hypochlorite‐responsive coordination complex Zn(DZ)3 is employed as the energy acceptor. The quenched upconversion luminescence, induced by the Zn(DZ)3 complex, can be efficiently recovered after addition of hypochlorite through the selective oxidative breakage of the Zn‐S‐C bonds in the Zn(DZ)3 complex, which was verified by mass spectrometry. The detection limit for hypochlorite of this sensing system is as low as 3 nM. Furthermore, this newly coordination‐complex engineered upconversion nanosensor is successfully applied to image different amounts of exogenous hypochlorite in living HeLa cells.